1993
DOI: 10.1016/0741-5214(93)90268-q
|View full text |Cite
|
Sign up to set email alerts
|

Femorofemoral bypass grafts: Analysis of patency and factors influencing long-term outcome

Abstract: In conclusion, FFBPG offers moderately low long-term patency in a population with limited survival. Outflow procedures performed concomitantly with FFBPG seemed to compensate for the negative impact on graft patency rate of ipsilateral SFA occlusion and limb-threatening ischemia. Limb-threatening ischemia, however, carried a significantly higher (p < 0.05) amputation rate. The influence of preoperative donor iliac artery percutaneous transluminal balloon angioplasty on FFBPG patency remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 19 publications
7
34
0
3
Order By: Relevance
“…Unilateral iliac percutaneous angioplasty and femoralfemoral bypass are associated with only slightly lower patency. In large series, patencies of 78% to 92% at 1 year and 66% at 7 years have been reported (514,515). Perler and Williams noted a similar patency for femoral-femoral bypass in the setting of unilateral iliac occlusion without donor limb disease, with patencies of 73% at 1 year and 59% at 5 and 7 years (515).…”
Section: Outflow Proceduresmentioning
confidence: 88%
“…Unilateral iliac percutaneous angioplasty and femoralfemoral bypass are associated with only slightly lower patency. In large series, patencies of 78% to 92% at 1 year and 66% at 7 years have been reported (514,515). Perler and Williams noted a similar patency for femoral-femoral bypass in the setting of unilateral iliac occlusion without donor limb disease, with patencies of 73% at 1 year and 59% at 5 and 7 years (515).…”
Section: Outflow Proceduresmentioning
confidence: 88%
“…Their assertion is based on studies reporting patency rates of crossover bypasses in patients with peripheral occlusive arterial disease. [20][21][22][23][24][25][26][27][28][29][30] These speculations are hypothetical because crossover bypass for AUI endografting is performed in patients with aneurysmatic disease who usually do not have peripheral occlusive disease. 1 In this study, only one case of femoral-femoral bypass thrombosis was observed and it was secondary to thrombosis of the terminaliliac part of the AUI endograft due to severe stenosis of the native artery.…”
Section: Discussionmentioning
confidence: 99%